(untitled) - Graubard, Mark (Minneapolis, 1967)
The result is that science is presented in our best educational institutions as the end result of a process, with little attention to the actual strucggle and search for scientific knowledge which man has pursued since his earliest history.
Keywords: Science,Khoa học; History,Lịch sử